Metabolomics of cell lines: a tool for aging research - Rocha, Ana Filipa Seixas Fonte da (2020)
The world is aging and therefore it is essential to understand how the development of this process in organisms is, especially in human beings. Its knowing that this phenomenon does not occur in the same way in all individuals, and that there are some with a chronological age of 80 years and yet, they present a condition of a younger subject. Thus, it is essential to join efforts to understand this event. Currently, there are several models for the study of those process, from animal models, to computational or cellular models, with the latter having more advantages. Cell models, namely cell models of fibroblasts, are thus increasingly used for metabolomics research in the aging research since through these techniques we are able to indirectly study the pathways of this process, since this gives valuable insights into the composition of metabolites present in a sample. An approach that combines several of these tools, such as FTIR, MS or NMR, will be an asset and will allow for the study of aging at a molecular level and possible reveal new discoveries.